Os impactos da lei n 14.430/2022 sobre as operaç\~oes de securitizaç\~ao no Brasil - Camillo de Moraes Bassi (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– In this Discussion Paper, the main impacts of Law No. 14/430/2022 on securitization operations in Brazil are discussed. Focusing on securitization companies, it documents how the "Single Law" of financial technique interfered in their operational system, in order to position these operations on the same level. It is concluded that this homogenization movement will boost the securitization market, until then, occupied by Real Estate Receivables Certificates (CRI) and Agribusiness Receivables Certificates (CRA).
Keywords: G18; 330; securitization; Brazil